Developing on Implant Biorubber Materials without Using Acid for Coagulation - Punyanitya, Sittiporn; Koonawut, Rungsarid; Sirisoam, Tiwasawat (Greater Mekong Subregion Medical Journal, 2021)
Background: Natural rubber latex (NRL) from Hevea brasiliensis is a colloidal anionic system formed by rubber particles (1,4-cis-polyisoprene) stabilized by phospholipids and protein molecules. Rubber biomaterials using as a novel technology could develop to apply as biomaterial based on a new manufacturing process, several new biomedical applications have been proposed since NRL is very biocompatible, stimulating cellular adhesion, the formation of the extracellular matrix, and promoting the replacement and regeneration of tissue. Objective: This study aimed to deproteinization from fresh natural rubber latex (NRL) and to coagulate the deproteinized natural rubber latex (DNRL) for using as implant biomaterials with novel technology without using acid for coagulation. Methods: Coagulated DNRL films is often used to prepare the blended films by solutioncasting technique. Its films presents interesting physical properties in elasticity. Results: The deproteinized NRL containing various CaO gave lower modulus values comparing with the control films. Conclusion: In this experiment, the blended films of DNRL and various CaO could form appropriate films. The physical and mechanical properties of the blended films depended on type and content of CaO addition. From the good elasticity of blended films, they could develop to apply as the production of a biomaterial of NRL that has been used to replace vessels, esophagus, pericardium, and abdominal wall.